Laparoscopic fundoplication and new aspects of neural anatomy at the oesophagogastric junction. Issue 3 (5th March 2020) - Gehwolf, P.; Renz, O.; Brenner, E.; Cardini, B.; Lorenz, A.; Wykypiel, H.
Abstract : Background: In fundoplication, mobilization of the distal oesophagus and proximal stomach is essential to obtain a sufficient tension‐free intra‐abdominal oesophageal length for creation of an efficient antireflux barrier. Most surgical literature and anatomical illustrations do not describe nerve branches running from the diaphragm to the stomach. After observing small nerve branches at laparoscopic fundoplication, penetrating the left crus of the diaphragm lateral to the hiatus and apparently running into the stomach, an anatomical cadaver study was undertaken to identify the origin and target organ of these nerves. Methods: Fifty‐three human cadavers (23 men, 30 women; age range 35–103 years) were dissected with special attention to the nerves that penetrate the left crus of the diaphragm. The entire course of these nerves was documented with standardized drawings and photos. Results: Small nerve branches penetrating the diaphragm lateral to the left crus of the hiatus were found in 17 (32 per cent) of the 53 cadavers. In 14 of these 17 cadavers, one or two splanchnic nerve branches were identified, and in ten of the 17 the nerve branches were found to be phrenic nerves. In seven of these 17 cadavers, two different nerve branches were found and assigned to both splanchnic and phrenic nerves. Conclusion: Nerves penetrating the left crus with splanchnic origin or phrenic origin have been identified. Their function remains unclear and their relationship to postfundoplication symptoms remains to be determined. Abstract : Small nerve branches penetrating the left crus of the diaphragm lateral to the hiatus, presumably running into the stomach, were observed during surgery. These nerve branches were allocated to the splanchnic and phrenic nerves. The origins and target organs of these nerves were identified. Their role in postfundoplication complaints is discussed. Nerves that might influence outcome. Abstract : Antecedentes: A la hora de realizar una fundoplicatura, la movilización del esófago distal y del estómago proximal es esencial para obtener una longitud de esófago intraabdominal suficiente y sin tensión para crear una barrera antirreflujo eficiente. La mayoría de la literatura quirúrgica y de las ilustraciones anatómicas no describen unas ramas nerviosas que discurren desde el diafragma al estómago. Tras observar pequeñas ramas nerviosas durante la realización de una fundoplicatura laparoscópica que penetran la crura izquierda del diafragma lateral al hiato y que aparentemente discurren hacia el estómago, se llevó a cabo un estudio anatómico en cadáver para identificar el origen y el órgano diana de estos nervios. Métodos: Se diseccionaron 53 cadáveres humanos (23 varones, 30 mujeres, rango de edad: 35‐103 años) con especial atención hacia los nervios que penetran la crura izquierda del diafragma. Se documentó el recorrido completo de estos nervios con fotos y dibujos de una forma estandarizada. Resultados: En 17 (32%) de 53 cadáveres se hallaron pequeñas ramas nerviosas que penetraban el diafragma lateral a la crura izquierda del hiato. En 14 cadáveres (de los 17) se identificaron una o dos ramas nerviosas esplácnicas, y en 10 de los 17 cadáveres las ramas nerviosas que se hallaron resultaron ser nervios frénicos. En 7 de estos 17 cadáveres, se hallaron dos ramas nerviosas diferentes y se asignaron a ambos nervios, esplácnicos y frénicos. Conclusión: Se han identificado los nervios que penetran la crura izquierda con un origen esplácnico y frénico. Sus funciones están por aclarar, así como su relación con los síntomas que aparecen tras la fundoplicatura.